The Effect of Profitability on the Stock Price of Banking Companies in 2019-2024 - Dinar Trininda Maria Haning; Resvina Situmorang (CV. Namora dan Riona Bersaudara, 2026)
This study examines the effect of Return on Assets (ROA), Return on Equity (ROE), and Earnings per Share (EPS) on the stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period, which covers the pre-COVID, COVID, and post-COVID phases. Using a quantitative approach, multiple linear regression is applied to secondary data obtained from annual financial statements and closing stock prices. The results show that EPS has a positive and significant effect on stock prices, while ROA and ROE do not exhibit significant partial effects; however, the three profitability indicators simultaneously influence stock prices. Phase-based analysis further reveals that EPS and stock prices declined during the COVID-19 period and recovered in the post-pandemic phase, confirming that the pandemic created a structural shock to banking performance and investor behavior. The findings strengthen signaling theory by emphasizing earnings per share as the most relevant financial signal in banking stock valuation. Practically, this study provides insights for investors in making informed investment decisions, for banking management in maintaining sustainable profitability, and for regulators in enhancing transparency and the quality of financial reporting in the Indonesian capital market.